Analysis of Financial Ratios and ESG on Stock Returns with Firm Value as a Moderating Variable - Agustin, Sefhia; Febriyani, Diana; Mahadianto, Moh Yudi (Rescollacom (Research Collaborations Community), 2025)
The purpose of this research is to examine the relationship between financial ratios, environmental, social, and governance (ESG) factors, and the stock returns of 2020–2023 IDX ESG Leaders businesses, controlling for company valuation. We use a quantitative descriptive approach with a 26-company purposive sample. Using SPSS, we ran multiple linear regressions on the secondary data. In order to ensure that the findings are still valid, we eliminated one outlier. Stock returns are unaffected by ESG Disclosure, ROA, or DER, but are significantly impacted negatively by Current Ratio (CR). According to the moderation test, the impact of ROA on stock returns can only be mitigated by considering corporate value. Therefore, a high level of profitability backed by a solid firm value may make investors more interested. The research here is time-bound, and it relies on secondary ESG data. It would be wise to include more variables and data in the future. Investors and management may use these results as a benchmark for evaluating stock performance and highlighting the need of increasing business transparency and value.